Designing Novel Angiotensin Receptor Blockers and their Antihypertensive Potentials - Malsawmzela, Denis; Lalthanpuii, Pawi B.; L, Lalnunhruaitluangi; Sailo, Lalzikpuii; Lalruatfela, Bawitlung; Lalchhandama, Kholhring (Asian Journal of Biological and Life Sciences)
Background: Hypertension is a pervasive and incurable disease that requires an effective management throughout life. Sartans are the most commonly used prescription drugs. These drugs are specific angiotensin II receptor type 1 (AT1R) antagonists and are commonly called Angiotensin Receptor Blockers (ARBs). However, further development of the drugs is necessary since none of the sartans that are clinically available possess all the desired pharmacological properties such as bioavailability, high efficacy and safety. Materials and Methods: Five novel AT1R antagonists were computationally designed using the molecular configuration of olmesartan as a base molecule. The compounds were analyzed in silico for their pharmacodynamics, pharmacokinetics, toxicity, druglikeness, binding affinity to AT1R and molecular dynamics. Results: Among the novel compounds, compound 1, 2 and 3 showed promising properties as effective and safe ARBs. Compound 4 is unsuitable for further development due to its high molecular weight, high toxicity and low pharmacological activities. Compound 5 also lacked many of the desired drug properties and showed high toxicity and mutagenicity. Conclusion: Compound 1, 2 and 3 appeared to have AT1R antagonistic activity and pharmacological properties to be developed as antihypertensive compounds. The findings encourage further investigations into the precise mode of action and experimental tests for the novel compounds.
Keywords: Angiotensin II receptor type 1 blockers; Hypertension; Molecular docking; Molecular dynamic simulation; Toxicity.